When They Severed Earth from Sky : How the Human Mind Shapes Myth. - Barber, E. J. W., 1940-; Barber, Paul, 1941- (Princeton University Press, 2011)
Why were Prometheus and Loki envisioned as chained to rocks? What was the Golden Calf? Why are mirrors believed to carry bad luck? How could anyone think that mortals like Perseus, Beowulf, and St. George actually fought dragons, since dragons don't exist? Strange though they sound, however, these "myths" did not begin as fiction. This absorbing book shows that myths originally transmitted real information about real events and observations, preserving the information sometimes for millennia within nonliterate societies. Geologists' interpretations of how a volcanic cataclysm long ago created.